Cinquecento sogni e un questionario. Sull’attività onirica degli adolescenti durante il primo lockdown - Bonizzi, Caterina; Guerero-Gomez, Ana; Homberg, Annelore; Iannaco, Cecilia (Il sogno della farfalla, 2021)
The authors of this paper discuss the similarities and differences between international dream research and the conception of dreams according to Fagioli’s Theory of Birth. The paper particularly focuses on the results of a questionnaire on dream activity administered to 2105 Italian, Romanian and Croatian students during the Covid-19 lockdown in spring 2020. Among all the students, 468 agreed on writing a dream brief description. The aim of the survey was to investigate whether adolescents’ dreams had been affected by the exceptional and potentially traumatic lockdown circumstances. Considering the answers to the questionnaire, what emerges is a fair emotional and relational resilience experienced by the adolescents during the first pandemic wave. However, one fifth of the participants reported an increase in the number of nightmares. These events were particularly recurrent in girls and older adolescents and were associated to subjective stress characterized by emotional states of anger and sadness. At the same time, equally stressful events such as the illness or death of a close person due to Covid-19 infection did not seem to present the same correlation. The article ends by mentioning about the role of dream activity investigation as a possible form of psychiatric primary prevention and as a tool to preserve adolescent’s well-being after the pandemic.